Dispute avoidance in Islamic banking industry in Malaysia: A preliminary exposition - Abdul-Qadir Zubair, Aishat; Oseni, Umar Aimhanosi; Engku Ali, Engku Rabiah Adawiah; Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib (2013)
The Malaysian Islamic banking sector has continued to experience a robust growth with Islamic banking assets market share increasing to about 20.0% as at November 2012 from 18.8% recorded in 2011. Based on this growth, KFH-Research projects Islamic financing facilities in Malaysia to grow to RM 277.2 billion in 2013. They estimate that Malaysia’s Islamic banking assets contributed 10.0% of the total global Islamic banking assets in 2012. However if this growth is to be sustained, steps must be taken to put in place dispute avoidance processes to promote sustainable practices in the industry. This is because if disputes between parties in the industry are not avoided or properly managed, they may threaten the very existence of the industry and this may lead to loss of interest in the industry since it is operating in a competitive environment. This paper introduces a number of dispute avoidance processes (DAP) that may be considered in the Islamic banking industry to promote best practices. Such processes are put in place to prevent and deescalate budding disputes from the contract to performance stage. Some insights are drawn from the successes recorded in the construction industry in Malaysia and beyond where sustainable mechanisms have been put in place to effectively manage disputes as they arise. While drawing from some DAP in the classical Islamic law modelled after concepts of Naṣīḥah (expert advice) and Muḥtasib (ombudsman), this study examines the various proactive measures that can be put in place to help manage and avoid disputes before they escalate into legal battles in the courtroom. This study therefore proposes for the development of DAP in the Malaysian Islamic banking industry.